ANALISIS KEBUTUHAN PENGEMBANGAN MODUL LITERASI EKOLOGI LAHAN BASAH BERBASIS INKUIRI UNTUK MAHASISWA PENDIDIKAN GEOGRAFI ULM - Setiawan, Faisal Arif; Rahman, Akhmad Munaya; Renaldi, Adriyan (Jurnal Spasial, 2024)
This study aims to analyze student needs for teaching materials used in lecture activities. This research is a descriptive study with the subject of this research is the third semester geography education students of FKIP Lambung Mangkurat University as many as 85 students. The research data was obtained from filling out a questionnaire on the need for teaching materials. Data analysis using percentages. The results from the questionnaire indicate that the need for a non-project-based learning module is what students want (76%). The learning module is able to make students learn independently so that they support their lecture activities.